KESIAPAN PERGURUAN TINGGI DALAM PENERAPAN KEBIJAKAN MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) (Studi Kasus pada Perguruan Tinggi STKIP Adzkia) - Adriantoni Adriantoni (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2022)
This study aimed to find the preparation of the university in implementing Independent Campus Learning policy (MBKM) for both programs, human resources, and infrastructure. The approach of this study was Qualitative, and the collecting of the data used interviews, observation, and documentation. The analysis of the data used triangulation data. It was used to get validity and detailed information of the data. The result of the study got from the program aspects that had been implemented. They were a teacher and teaching training programs. It found there were fewer human resources and infrastructure in implementing Independent Campus Learning policy (MBKM)